Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep18379
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of flagellin as a stimulator of innate immunity

Abstract: We report the development of a well-defined flagellin-based nanoparticle stimulator and also provide a new mechanism of action model explaining how flagellin-triggered innate immunity has evolved to favor localized rather than potentially debilitating systemic immune stimulation. Cell-free protein synthesis (CFPS) was used to facilitate mutational analysis and precisely orientated display of flagellin on Hepatitis B core (HBc) protein virus-like particles (VLPs). The need for product stability and an understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
1
33
0
1
Order By: Relevance
“…In S . Enteritidis FliC this region is embedded within flagellar filament and it is not surface exposed [ 32 ]. The incorporation of the TLR5 binding region from S .…”
Section: Discussionmentioning
confidence: 99%
“…In S . Enteritidis FliC this region is embedded within flagellar filament and it is not surface exposed [ 32 ]. The incorporation of the TLR5 binding region from S .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the case of neural stimulation, the performance of graphene‐based materials for recording applications can greatly improve by using structured or 3D films that increase the specific surface area of the electrode. This has been recently shown by recording in vivo brain activity using porous graphene‐related materials with a good signal‐to‐noise ratio.…”
Section: Graphene Materials For Next‐generation Neural Interfacesmentioning
confidence: 95%
“…However, recent studies have shown that when used in porous thin‐films processed from flakes or introduced in polymer composites, graphene‐based materials can exhibit dramatically improved performance for neural stimulation. For instance, porous graphene oxide electrodes reduced by laser treatment and by the Langmuir–Blodgett method have been reported to be able to stimulate neural tissues with outstanding charge injection values between 1 and 3 mC cm −2 . Furthermore, new promising materials are expected to emerge from the very active research field of the supercapacitors, in which graphene‐based materials exhibiting very large active surface area are being developed achieving very high double layer capacitance.…”
Section: Graphene Materials For Next‐generation Neural Interfacesmentioning
confidence: 99%
“…To enhance its immunogenicity, we fused Bet v 1 to flagellin from Salmonella typhimurium (fliC) because the immunostimulatory capacity of this flagellin has been proved in various studies. 22 We substituted its hypervariable region, which is thought to promote production of neutralizing antibodies 23 that downregulate TLR5 signaling, with a short-turn motif to reduce its size and to keep the close proximity of the N-and C-termini necessary for TLR5 binding. Deletion of the hypervariable region did not abrogate the adjuvant effect because the resulting truncated flagellin, NtCFlg, still activated TLR5 and was fused to either the N-or C-terminus of Bet v 1, which was termed NtCFlg-Bet v 1 and Bet v 1-NtCFlg, respectively, to assess possible position effects.…”
mentioning
confidence: 99%